Heart rate measured during heat ramp exposure experiments of the European oyster, Ostrea edulis - Götze, Sandra; Reddin, Carl; Ketelsen, Isabel; Busack, Michael; Lannig, Gisela; Bock, Christian; Pörtner, Hans-Otto (PANGAEA, 2025)
This dataset contains heart rate data measured during heat ramp experiments of the European oyster, Ostrea edulis. We studied organismal and heart tissue cellular responses of the European oyster, Ostrea edulis, challenged by rapid warming (+2°C/h) and gradual warming (+2°C/24h). Specimens were collected as wild adults from the estuary of the Ría de Ferrol (Spain, 43°27.64'N and 8°12.04'W) in October 2020 and March 2021. Cardiac activity was monitored using infrared photoplethysmography. An Optocoupler Vishay CNY-70 sensor was placed directly above the heart and glued to the shell with coral glue (EcoTech Elements). Plethysmographs were connected to a PowerLab (ADInstruments, Australia) signal recording system and heart beats were manually counted using LabChart (ADInstruments, Australia). See manuscript for further methodological details and results interpretation.
Keywords: Bivalve; Europe; European flat oyster; heart; Laboratory experiment; Ocean climate change; photoplethysmograph; temperature ramp